An overview of methane emissions in constructed wetlands: how do plants influence methane flux during the wastewater treatment?. Issue 1 (1st January 2019) - Xu, Guangming; Li, Yue; Wang, Sen; Kong, Fanlong; Yu, Zhengda
Abstract: Plants play an essential role in methane (CH4 ) production, transport and release processes of constructed wetlands but as yet there has been no consistent and clear consensus of their impacts on CH4 emissions. In this study, we used plant presence, species richness, plant species-specificity, and harvesting activity information obtained by reviewing papers published from 1993 to 2018 to elucidate the key factors that drive CH4 emission from constructed wetlands. Although it was not statistically significant, plant presence increased the CH4 emissions compared to unvegetated conditions and relatively lower values were observed for constructed wetlands planted with Acorus calamus, Cyperus papyrus or Juncus effusus . The use of a single plant species not only changed the production and consumption of CH4 by affecting the functioning of roots but also influenced the process of CH4 entering the atmosphere under different transport capacities. The CH4 flux reached 1.0686 g CH4 m −2 d −1 from the Zizania latifolia system, which is eight times larger than that of the Phalaris arundinacea system. The mixed systems exhibited a positive increase in CH4 flux with plant species richness due to the complementary effects of the root exudates excreted from different plants. The minimum CH4 value (−0.0084 g CH4 m −2 d −1 ) was observed in the three-species system ( Oenanthe javanica, Phalaris arundinacea and J. effusus ). These results demonstrate that selecting several species with lower methane fluxes such as Typha latifolia and C. papyrus and suitably regulating harvesting in constructed wetlands can be more effective for mitigating the potential of CH4 emissions while maintaining the efficiency of sewage purification.